El Dorado Drive : a novel [large type] - Abbott, Megan, 1971- (Random House Large Print, 2025)
"The three Bishop sisters grew up in privilege in the moneyed suburbs of Detroit. But as the auto industry declined, so did their fortunes. Harper, the youngest, is barely making ends meet when her beloved, charismatic sister Pam-currently in the middle of a contentious battle with her ex-husband-and her eldest sister, Debra, approach her about joining an exciting new club. The Wheel offers women like themselves-middle-aged and of declining means-a way to make their own money, independent of husbands or families. Quickly, however, the Wheel's success, and their own addiction to it, leads to greater and greater risks-and a crime so shocking it threatens to bring everything down with it"--Page 4 of cover.